Development of a power operated rubber tapping machine - ASWATHY M. S; Soumya Krishnan V; Sruthi N. U; Er. George Mathew (Guide) (Tavanur 2016 Department of Food and Agricultural Processing Engineering)
Development of a power operated rubber tapping machine
Development of a power operated rubber tapping machine